An aorgic expression of desire, the cold romanticism of Paul Klee. A genealogical and genetic approximation to his thought-in-image - Martínez Vilajuana, Sergio (Escritura e Imagen, 2019)
In this work we will seek to suggest that an aorgic expression of desire is what present the so called cold romanticism of Paul Klee. On the one hand, this expression discovered her source in the late Hölderlin and this implied that there is a tragic background in the thought of Klee. On the other hand, it would be necessary to exposed the link between the cold romanticism of Klee and the early german romanticism. Specifically, about the significance of the experience of the work of art. However, at the same time, we will consider a distance in respect to that early movement and the late Hölderin that nourish that aorgic expression of desire, distance that could be described through a merging of Nietzsche in Klee’s atmosphere [Stimmung]. But, also, we haved to deal with what elaborated the painter and draftsman: a thought-in-image inasmuch as its an experience of a thought whose nature is apropositional. This thought, under the sign of that distance, experiment what we have to name: a chaos-cosmos.
Keywords: aorgic expression of desire; cold romanticism; early romanticism; work of art; Hölderlin; Nietzsche; thought-in-image; chaos-cosmos